2018
DOI: 10.1515/erj-2018-0283
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Effect of Environmental Dynamism on the Relationship between a Firm’s Entrepreneurial Orientation and Financial Performance

Abstract: The relationship between entrepreneurial orientation and firm performance has been the focus of numerous empirical studies over the past decade. The conclusions and findings reported are diverse and often conflicting. One possible explanation for mixed findings is that past studies do not take into account the dynamic nature of the industry environment. Using a sample of 192 Swiss firms from several different industries, this study examines the direct effect of entrepreneurial orientation on financial firm per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 89 publications
4
30
3
2
Order By: Relevance
“…The structural equation analysis could not prove these moderation relationships. This result is contrary to Tajeddini & Mueller (2018) who found that ED moderates the relationship between EO and the FP, using a sample of 192 Swiss firms from several industries. One possible explanation is that CE has boundary conditions associated with the context of each country (Demirkan et al, 2019;Liu & Vrontis, 2017;Miller, 2011).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The structural equation analysis could not prove these moderation relationships. This result is contrary to Tajeddini & Mueller (2018) who found that ED moderates the relationship between EO and the FP, using a sample of 192 Swiss firms from several industries. One possible explanation is that CE has boundary conditions associated with the context of each country (Demirkan et al, 2019;Liu & Vrontis, 2017;Miller, 2011).…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, hypothesis 4 did not find support. This result was contrary to the results of Tajeddini & Mueller (2018) and Ambad & Wahab (2016), who found that ED moderated the relationship between EO and the FP. Additionally, the effect size (f 2 ) of the IT, ED-EO, is marginal (f 2 = 0.0005) [Cohen, 1988].…”
Section: Moderation Effect Of Ed Between the Relation Of Eo And Fp Ofcontrasting
confidence: 99%
See 3 more Smart Citations